2004
DOI: 10.1007/s10067-004-0896-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between walking time, quadriceps muscle strength and cardiovascular capacity in patients with rheumatoid arthritis and ankylosing spondylitis

Abstract: The aim of this study was to examine whether there are any associations between walking time, quadriceps muscle strength and cardiovascular capacity in patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Thirty-one patients with RA and 26 patients with AS belonging to Steinbrocker's functional class I-II were examined. Cardiovascular capacity was calculated from the expired air during a bicycle test and quadriceps muscle strength by the peak torque from an isokinetic dynamometer test. Walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…This study also found muscular endurance to be significantly decreased in the knee extensor and flexor groups. This has implications for performance of activities requiring repeated or prolonged lower-limb strength; walking speed has previously been found to be associated with quadriceps muscle strength [49]. Both muscular strength and endurance were significantly associated with participant reported physical function.…”
Section: Discussionmentioning
confidence: 91%
“…This study also found muscular endurance to be significantly decreased in the knee extensor and flexor groups. This has implications for performance of activities requiring repeated or prolonged lower-limb strength; walking speed has previously been found to be associated with quadriceps muscle strength [49]. Both muscular strength and endurance were significantly associated with participant reported physical function.…”
Section: Discussionmentioning
confidence: 91%
“…Quadriceps force is reduced in the fibrotic idiopathic interstitial pneumonias (IPF and non-specific interstitial pneumonia) [25], sarcoidosis [26,27] and rheumatoid arthritis [28], with average values that are 20-35% lower than healthy controls. Lower quadriceps force is consistently associated with reduced peak exercise capacity [26,29] and reduced functional exercise capacity [25,26,27,30,31], regardless of the underlying type of ILD. In some ILDs, peripheral muscle function appears to worsen as the disease progresses [27,32].…”
Section: The Problemmentioning
confidence: 99%
“…In contrast, other studies have detected no relationship between isokinetic muscle strength and pain intensity in RA patients. [24,35] In the current trial, no relationship was found between the PT ratios of the knee muscles and the VAS pain scores in the OA and RA patients. Since these patients did not have reduced muscle strength compared with the controls, it might not be possible to detect the relationship between muscle strength and pain severity from our findings.…”
Section: Discussionmentioning
confidence: 81%
“…In a study by Stucki et al, [36] a significant negative correlation was shown between disease activity and isometric muscle strength, whereas Mengshoel et al [35] reported no correlation. Our study determined that there was no correlation between disease activity and isokinetic muscle strength in patients with lower limb RA.…”
Section: Discussionmentioning
confidence: 98%